Gender and climate experts come together to address inequalities and climate resilience challenges in Nigeria’s agrifood systems - Enemali, Theophilus; Awinoh, Martha; Lecoutere, Els (CGIAR Initiative on Gender Equality, 2024)
On October 9, 2024, gender and climate experts gathered in Abuja for the third high-level dialogue on gender and climate change, convened by HER+, the CGIAR Gender Equality Research Initiative, to address gender equality and climate resilience challenges in Nigeria’s agrifood systems. The dialogue is the third in a series and continues the conversations of the first high-level dialogue organized in October 2022 in Nairobi, Kenya, and the second high-level dialogue that was held in October 2023 in New Delhi, India.